The Origins and Meanings of Names Describing Investment Practices that Integrate a Consideration of ESG Issues in the Academic Literature - Eccles, N. S.; Viviers, S. (2011)
The aim of this study was to reflect on the origins and meanings of names describing investment practices that integrate a consideration of environmental, social and corporate governance issues in the academic literature. A review of 190 academic papers spanning the period from 1975 to mid-2009 was conducted. This exploratory study evaluated the associations and disassociations of the primary name assigned to this genre of investment with variables grouped into five domains, namely Primary Ethical Position, Investment Strategy, Publication Date, Regions Covered and Periodical Type. The study indicated that papers coded as expressing a deontological ethical position were more frequently associated with the name Ethical Investment, whereas those with an ambiguous ethical position were less frequently associated with Ethical Investment. Three investment strategies (positive screening, best-in-class and cause-based investing) were unusually associated with the primary name Responsible Investment. A strong preference for the name Ethical Investment was noted in the United Kingdom, and contrasted starkly with an apparent aversion for this name in the United States. The name Ethical Investment is significantly more frequently used in journals dealing with ethics, business ethics and philosophy than in finance, economic and investment journals. Finally, the study yielded some weak hints that the name Responsible Investment might perhaps be linked to an egoist ethical position. On the basis of this, and because these have already been substantively linked through the Principles for Responsible Investment in the popular discourse, we follow the heuristic tradition set by Sparkes (Business Ethics Eur Rev 10:194–201, 2001), and propose that Responsible Investment be defined as ‘Investment practices that integrate a consideration of ESG issues with the primary purpose of delivering higher-risk-adjusted financial returns’.
Keywords: Naming; Egoism; Responsible investment; ethical investment; Socially Responsible Investment